Eating down or simply eating less? The diet and health implications of these practices during pregnancy and postpartum in rural Bangladesh. Issue 11 (20th June 2017) - Harding, Kassandra L; Matias, Susana L; Mridha, Malay K; Vosti, Stephen A; Hussain, Sohrab; Dewey, Kathryn G; Stewart, Christine P
Abstract: Objective: To: (i) determine the prevalence of self-reported eating less and eating down during early and late pregnancy and postpartum, and explore risk factors associated with eating less; (ii) examine the association between eating less and diet quality; and (iii) determine the association between eating less and weight gain during pregnancy. Design: Data were collected longitudinally from a cohort of women participating in a community health programme. Diet was assessed at three time points (≤20 weeks' gestation, 36 weeks' gestation, 6 months' postpartum), body weight was measured during study enrolment (≤20 weeks' gestation) and at 36 weeks' gestation, and information about the woman and her household was collected at enrolment. Setting: The Rang-Din Nutrition Study in the Rangpur and Dinajpur districts of Bangladesh. Subjects: Women ( n 4011). Results: The prevalence of self-reported eating less differed by time point (75·9 % in early pregnancy, 38·8 % in late pregnancy, 7·4 % postpartum; P <0·001). The most common reason for eating less across all time periods was food aversion or loss of appetite. Women who reported eating less in late pregnancy had consumed animal-source foods less frequently in the preceding week than women who reported eating more (mean (sd) : 11·7 (7·4) v . 14·8 (9·2) times/week; P <0·001) and had lower weekly weight gain than women who reported eating more (mean (se) : 0·27 (0·004) v . 0·33 (0·004) kg/week; P <0·001). Conclusions: Eating less has negative implications with respect to diet quality and pregnancy weight gain in this context.